Ganoderma lucidum effects in an animal model of obesity - Castro-Ribeiro, Carla (2021)
Obesity is a pandemic disease, and its evolution can be influenced by regular consumption of natural bioactive compounds. Mushrooms, such as Ganoderma lucidum (GL), include a wide variety of biomolecules with potential anti-obesity effects. This work aimed to study the influence of GL in an animal model of obesity. Forty-eight male mice (C57BL/6J) were divided into 5 groups: Group (G)-1-Western Control Diet; G-2-Western Diet 0.2% Cholesterol (WDC); G-3-WDC+0.7g/kg of GL; G-4-WDC+1.4g/kg of GL; G-5 WDC+2.8g/kg of GL. Water and food consumption were recorded weekly. Animals were weighed individually, and their temperature was measured on the back and abdomen (thermographic camera FLIRE6390). Thirteen weeks later, animals were sacrificed, and organs collected. A liver portion was used for histopathology analysis (ethical approval nº 8776). Chemical characterization of the GL extract was profiled by HPLC-DAD-ESI/MS. Ganoderic acid H and p-hydroxybenzoic acid were the main triterpenic and phenolic acids in the extract, respectively. Food and water consumption were no different among groups. All animals showed weight gain (11-16%): animals without GL supplementation showed the highest weight gain (G2 and G1, respectively); the groups with GL showed the lowest weight gain, which decreased as the mushroom concentration increased. Basal and final body temperatures remained constant. Liver weight was different among groups (p<0.05). Microvesicular (39/47; 83%) and macrovesicular fatty changes (steatosis) were the most frequent morphological changes in the liver. Hyperlipidemic diets consumption promoted weight gain and obesity. The higher weight gain in the groups not supplemented with GL suggested its anti-obesity properties. In this study, animals developed steatosis, which was not modified by GL supplementation. However, it should be noticed that the changes in lipid metabolism are reversible, and the differences observed in the liver relative weights, lower in the groups supplemented with GL, suggested an ongoing process of restoring to normal hepatocyte’s phenotype.